2020
DOI: 10.1111/jdv.16172
|View full text |Cite
|
Sign up to set email alerts
|

BRAF wild‐type recurrent indeterminate dendritic cell tumour presenting with leonine facies

Abstract: BRAF wild-type recurrent indeterminate dendritic cell tumour presenting with leonine facies Editor Indeterminate dendritic cell tumour (IDCT) was a rare histiocytosis originating from stromal dendritic accessory cells. 1 Only two studies have described leonine facies as the dominant feature of IDCTs. 2 Here, we report another IDCT presenting with leonine facies. A 37-year-old man presented with 4-year history of diffuse papules on his cheeks and then gradually spreading to his face, back and extremities. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Therefore, conducting more collective and in-depth studies is critical for clarifying the pathological mechanism of IDCT. First, patients with IDCT should be sent to large specialized medical centers, such as the Peking Union Medical College Hospital[ 13 ]. One reason is that it will be more convenient to conduct related clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, conducting more collective and in-depth studies is critical for clarifying the pathological mechanism of IDCT. First, patients with IDCT should be sent to large specialized medical centers, such as the Peking Union Medical College Hospital[ 13 ]. One reason is that it will be more convenient to conduct related clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…1 Only three cases have reported leonine facies as the major characteristic of IDCTs. 2 Here we report another case presented with typical leonine facies and generalized multiple confluent papules and nodules on the whole body without systemic involvement.…”
mentioning
confidence: 81%
“…:DOC 4 [ 21 ] Chen (2018) Male 31 MF N0 No MTX, no response, transfer to isotretinoin and thalidomide Improvement on skin, under follow up: SD 48 [ 17 ] Zhou (2019) Male 37 MF Yes No No Corticosteroids, vinca alkaloids, CTX Utilizing a range of treatments, yet constantly experiencing remission and relapse within 5 years. SD with RR 60 [ 16 ] Fischer (2021) Female 55 MF No No Thalidomide 6 months: lesion progress:PD 6 [ 15 ] Xu (2017) M MF No No Thalidomide PR 10 [ 18 ] Xu (2017) F 53 MF No No Methotrexate CR 10 [ 18 ] Xu (2017) M …”
Section: Literature Reviewmentioning
confidence: 99%
“…We reviewed the current examples of IDCT with cutaneous symptoms treated with chemotherapy medications to assess the efficacy and safety of chemotherapy drugs 1,5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] (Table 1). We found that remission and relapse occurred in 8 out of 26 chemotherapy-treated patients reported to date.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation